A new algorithm for face features extraction based on parametric contour and voronoi diagram - 559621 Dzulkifli Mohamad; Abbas Cheddad; International Conference on Information and Communication Technologies : from Theory to Applications (1st : 2004 : Damascus, Syria) (Skudai : Universiti Teknologi Malaysia, 2004)
40